Quando la popolazione “non partecipa”. Spunti per un’antropologia della vulnerabilità, del rischio e della responsabilità come contributo alle politiche sanitarie di controllo e prevenzione del dengue - Cerbini, Francesca (L'Uomo Società tradizione sviluppo, 2022)
In this article, I explore a very debated theme in scientific literature (in particular Brazilian) which describes, in synthesis, population’s noncompliance to dengue vector control policies, despite people usually show a high degree of knowledge about the contagion. I also consider how the anthropological sciences and the ethnographic research approach have been called into question in health promotion programs developed in the different contexts analyzed. This allows me to shed light on the growing involvement of anthropologists who are called to explore, in the local contexts, the meaning of the disease, of the infection and its mode of reproduction, and to point out the use and abuse of the term “culture” in such scenarios. In the conclusion, I propose to explain one of the main concerns emerged from literature, namely the lack of population’s participation to dengue control policies, in the light of an anthropology of vulnerability, risk and responsibility.